PENGARUH STRATEGI PEMBELAJARAN BERBASIS MASALAH DAN MODEL PENSEKORAN TERHADAP HASIL BELAJAR MATEMATIKA DENGAN MENGONTROL INTELIGENSI SISWA - Khasanah Khasanah (Akademika, 2016)
The study was aimed to find out the influence of problem-based learningstrategies and scoring models towards mathematics achievement by controllingstudents’ intelligence. The research method used in this study is an experimentalmethod. Meanwhile, the design used in this research was the factorial design ofand research hypotheses were tested by using covariant of analyses(ANCOVA). The participants of this study were 100 students from tenth grade inSMAN 55 and SMAN 60 Jakarta.The study concluded that after controlling students’ intelligence: (1)mathematics achievements of the students who were given the problem posingstrategy was higher than that of those who were given the problem solvingstrategy, (2) mathematics achievements of the students who were given the correctscore model was higher than that of those who were given the punishment scoremodel, (3) there was an interaction effect between problem-based learningstrategies and scoring models towards mathematics achievement, (4) especiallyfor groups of students who were given Problem Posing Strategy, mathematicsachievement of the students who were given the correct score model was higherthan that of those who were given the punishment score model, (5) especially forgroups of students who were given problem solving strategy, mathematicsachievement of the students who were given the correct score model was lowerthan that of those who were given the punishment score model, (6) especially forgroups of students who were given the correct score model, mathematicsachievement of the students who were given problem posing strategy was higherthan that of those who were given the problem solving strategy, and (7)especially for groups of students who were given the punishment score model,mathematics achievement of the students who were given the problem posingstrategy is lower than that of those who given the problem solving strategy. Thus,it can be recommended to the teachers to use the problem posing strategy and thecorrect score model.